Reproduction, mortality and growth of indigenous sheep and goats in Mozambique - McKinnon, D.; Rocha, A. (1985)
The comparative performances of Nguni sheep and Landim goats reared at Chobela Experimental Station are described. G.oats have the better reproductive performance, but both species are rather prolific. Late age at first parturition and long inter-parturition intervals seem to be a result of management, as recent results tend to show considerable improvement in these parameters. Sheep seem to be more seasonally affected than goats related to better periods for mating/lambing. Mortality rates are not as high as could be expected. No significant advantage in growth rate exists for sheep over goats in the early ages. Subjects for future investigation at station level are proposed. As investigations done on station may not reflect the actual situation in the traditional sector it is considered important to launch a programme of research at village level.